Working as a nurse in community health services during Covid-19: a qualitative study - Ellen Benestad Moi; Anne Valen Skisland; Berit Johannessen; Kristin Haraldstad; Gudrun Rohde; Sylvi Monika Flateland (BMC, 2022)
Abstract Background During the Covid-19 pandemic, new roles, increased workload, lack of staffing and infection control equipment, unclear infection control guidelines and conflicting information have led to uncertainty and unpredictability for health workers. Although community home-care nurses have been exposed to a range of personal and professional stressors during the pandemic, few studies have focused on their experiences. The aim of this study was to explore how Norwegian home-care nurses experienced the first wave of the Covid-19 pandemic. This knowledge may contribute to preparations for meetings with patients in future pandemics, how management can support its employees and how to structure a successful organization. Methods This study was a qualitative descriptive design comprising 12 semi-structured individual interviews with home-care nurses. A thematic analysis was carried out. Results Four main themes and 11 subthemes were constructed. The results revealed challenges related both to the organization and to management, experiences of unclear information, lack of available equipment, redeployment of staff and increased workload. Furthermore, it was challenging to provide high qualitative care. The nurses missed collegial togetherness and had feelings of uncertainty with a great fear of infecting others. Positive consequences were feelings of being valued and a greater awareness of infection control. Conclusion This study highlighted the importance of unambiguous information and clear delegation of responsibility, and that enough infection control equipment will likely minimize the fear of infecting each other. Being visible and admired for their work was important for the nurses' psychological well-being. Nurses, nursing managers and policymakers in community health care can use these results to develop strategies for future pandemic planning.